Identification of marine sponges-symbiotic bacteria and their application in degrading polycyclic aromatic hydrocarbons - ISMAIL MARZUKI; MUDYAWATI KAMARUDDIN; Rasheed Ahmad (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Marzuki I, Kamaruddin M, Ahmad R. 2021. Identification of marine sponges-symbiotic bacteria and their application in degrading polycyclic aromatic hydrocarbons. Biodiversitas 22: 1481-1488. Diverse and abundant microbial species that occupy marine sponges may make important contributions to host metabolism. Sponges are filter feeders and devour microorganisms from the seawater around them. Each microbe that endures the sponges’ digestive and immune responses are related symbiotically. Marine sponges symbiont bacteria can comprise as much as 40% of sponge tissue volume, and these are known to exhibit a great potential on polycyclic aromatic hydrocarbons (PAHs) degradation. However, the potential use of marine sponges symbiont bacteria is unexplored. Therefore, we designed and conducted a study to identify bacterial isolates obtained from sponges. For this, we collected sponges samples (Hyrtios erectus, Clathria (Thalysias) reinwardti), Niphates sp., and Callyspongia sp.) from the Spermonde islands in Indonesia. We successfully found eight bacterial isolates from four sponges, as molecular identification based on 16S rRNA approach revealed bacterial isolates of SpAB1, SpAB2, SpBB1, SpDB1, and SpDB2 from three sponges (Hyrtios erectus, Clathria (Thalysias) reinwardti), Niphates sp.). Interestingly, these were closely related to Pseudomonas, and a bacterial isolate from Callyspongia sp. (SpCB1) showed similarity to Bacillus. Bacillus and Pseudomonas bacteria isolated from hydrocarbon-contaminated sponges exhibited degradation of naphthalene and pyrene PAHs.